Skin Lesions Caused by Venomous Animals - Haddad, Vidal [UNESP] (Springer Nature, 2023)
Venomous and poisonous animals are those that can provoke envenomations in humans by utilizing body toxins. These substances can be injected or ingested by the victims, and occasionally, the envenomations can be associated with work activities. Most manifestations present lesions on the skin, and the most important and frequent situations are discussed in this chapter, including injuries in farmers, workers in forest areas, and fishermen. The therapeutic measures are indicated as well as accident prevention campaigns that could change the profile currently observed in the workforce and general population who encounter the risk of temporary contact. Most studies show repercussions on the skin of the victim, highlighting the importance of the dermatologist’s role in solving the problem.
Keywords: Bites and stings; Farmers; Fishermen; Forest; Occupational injuries; Venomous animals; Venomous fish